Characteristics and risk factors associated with work zone crashes - Akepati, Sreekanth Reddy (Kansas State University, 2010)
In the United States, approximately 1,100 people die and 40,000 people are injured annually as a result of motor vehicle crashes in work zones. These numbers may be a result of interruption to regular traffic flow caused by closed traffic lanes, poor traffic management within work zones, general misunderstanding of problems associated with work zones, or improper usage of traffic control devices. In regard to safety of work zones, this study was conducted to identify characteristics and risk factors associated with work zone crashes in Iowa, Kansas, Missouri, Nebraska and Wisconsin, states currently included in the Smart Work Zone Deployment Initiative (SWZDI) region. The study was conducted in two stages. In the first stage, characteristics and contributory causes related to work zone crashes such as environmental conditions, vehicles, crashes, drivers, and roadways were analyzed for the five states for the period 2002-2006. An analysis of percentage-wise distributions was carried out for each variable based on different conditions. Results showed that most of the work zone crashes occurred under clear environmental conditions as during daylight, no adverse weather, etc. Multiple-vehicle crashes were more predominant than single-vehicle crashes in work zone crashes. Primary driver-contributing factors of work zone crashes were inattentive driving, following too close for conditions, failure to yield right of way, driving too fast for conditions, and exceeding posted speed limits within work zones. A test of independency was performed to find the relation between crash severity and other work zone variables for the combined states. In the second stage, a statistical model was developed to identify risk factors associated with work zone crashes. In order to predict injury severity of work zone crashes, an ordered probit model analysis was carried out using the Iowa work zone crash database. According to findings of the severity model, work zone crashes involving trucks, light duty vehicles, vehicles following too close, sideswipe collisions of same-direction vehicles, nondeployment of airbags, and driver age are some of the contributing factors towards more severe crashes.
Keywords: work zone safety; risk factors; Engineering, Civil (0543)